Effect of a smartphone-based physical intervention on depression, fitness factors and movement characteristics in adults - Hyungsook Kim; David Michael O'Sullivan (BMC, 2024)
Abstract Background Physical activity has been shown to correlate with mental health and a reduction in symptoms of depression. However, the majority of research has focused only on the effects of either aerobic or nonaerobic exercise on depressive symptoms, while the use of novel technological innovations such as mobile phone-based activity programs and their effects on movement characteristics are underrepresented. This study had two objectives: (1) to investigate how effectively 4 weeks of mobile phone-based physical activity can affect depressive scores (CES-10-D and PHQ) and fitness levels and (2) to investigate the whether 4 weeks of mobile phone-based physical activity affected participants' movement characteristics. Methods A total of 31 participants were included and divided into an exercise group (n = 21) and a control group (n = 10). The exercise group was instructed to use a mobile phone-based exercise program 5 times per week for 4 weeks. Pre- and post-exercise, the participants' depression score (CES-10-D, PHQ9), fitness level (YMCA, grip strength) and movement characteristics (postural sway, movement ROM, movement speeds, etc.) for three Azure Kinect physical activity games based on different fitness factors (balance game, cardiovascular game, reaction game) were measured. Results Mixed model ANOVA revealed significant differences between pre- and post-intervention depression scores on the PHQ9 (P = .001) and CES-10-D (P < .001) in both the exercise group and the control group, but not between groups. In terms of movement characteristics, there was an increase in body sway (P = .045) and vertical head movement (P = .02) in the cardiovascular game jogging condition for the exercise group. In the reaction game, the exercise group showed a significant reduction in the number of mistakes (P = .03). There were no other significant differences for the other variables. Conclusion The results revealed no differences in the reduction in depression scores between the exercise group and the control group. However, this study showed that a mobile phone-based physical activity intervention affects in-game movement characteristics such as body sway and vertical head movement and therefore may show the potential of using activity-promoting mobile games for improving movement.